Sensing and deceiving an analysis of pseudo-news blogs and their readership - Posadas, Sinta 1992-
"Using the concepts of sense-making and self-deception, this thesis analyzes the link between the Communicative Purpose and structural features of satirical or pseudo-news blogs with the uses and gratifications of the readers of these blogs. To identify their Communicative Purpose and structural features, the blogs were analyzed according to the Rules, Relations and Codes stipulated in Jon Schmidt's (2007) blogging practices framework. The reader's uses and gratifications expectations were determined through the Uses and Gratifications Expectancy Model by Mondi, Woods and Rafi (2008). Results revealed that the blogs can influence the reader's formulation of expectations, leading them to perform either sense-making or self-deceptive activities."